Expert nurses' coping strategies in ethically challenging situations: a qualitative study - Yeon Hee Kim; Young-ah Kang; Jeong Hui Ok; Kwisoon Choe (BMC, 2021)
Abstract Background Nurses frequently encounter ethically challenging situations in everyday practice. In these situations, nurses often know an appropriate course of action to take but are unable to do so. Many studies have examined the ethically challenging situations faced by nurses, but how nurses cope with these situations is not well understood. Therefore, this study aims to explore the coping strategies used or adopted in ethically challenging situations by expert nurses in South Korea. Methods Participants were recruited via purposive sampling. Small group interviews were conducted with 26 expert registered nurses in a general hospital in South Korea. The data were analyzed using Giorgi's descriptive phenomenological method. Results The essential theme of nurses' experience of coping with ethically challenging situations was "being faithful to the nature of caring." This essential theme comprised three themes: self-monitoring of ethical insensitivity, maintaining honesty, and actively acting as an advocate. Conclusions The findings of this study suggest that the coping strategies of expert nurses are mostly consistent with the attributes of ethical competence as previously defined in healthcare, and expert nurses can address ethically challenging situations in an effective and ethical manner by faithfully adhering to the spirit of caring. System-wide early counseling and interventions should be considered for nurses who have experienced ethical difficulties.